The Role of Information Technology In Accomplishing the Need of Human Resource Function For the Multi Divisional Organisation.: Enhancing Human Resource Function through Information Technology (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The competition among the companies is actually the competition ofhuman resources, as the market reveals. A company, as a profit-pursuingorganization, is always under the pressure of delivering new products to winmarket share. Without high quality human resources and its effectivefunctioning, a company can hardly endure the profit pressure and pursue itslong term business strategy. The past decades has witnessed the transition of employeebecoming the most precious capital in the company and the ascent of HumanResource Management (HRM). The strengthened management of human resources isnow the very essence of a successful business story. Nowadays, business worldis undergoing a substantial change: the employee turn-over rate becomes high,and both the organization structure and management pattern change as well. Thetraditional HRM style fails to catch up with such rapid changes: thetraditional style mainly focuses on supportive personnel activities for acompany, for example, collecting employee information, monitoring individualperformance, and implementing organization policies.